Optimalisasi Zakat Perusahaan sebagai Instrumen Pengurang Pajak dalam Mendukung Pemerataan Ekonomi - Nor Anina; Nor Hikmah Sari; Muhammad Sauqi; Muh Arief Budiman (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
The implementation of corporate zakat in Indonesia remains relatively low despite its significant potential to support national economic development. This study aims to analyze the strategic role of corporate zakat as an instrument for reducing tax burdens and its contribution to economic equality. This research employs a literature review approach by examining relevant academic sources. The findings indicate that corporate zakat of 2.5% is obligatory for business entities that meet the nisab and haul requirements. Based on Law No. 23 of 2011 and Law No. 36 of 2008, zakat distributed through authorized institutions such as BAZNAS or LAZ can be deducted from taxable income. Corporate zakat not only fulfills religious obligations but also plays a vital role in wealth redistribution through social assistance and productive capital for mustahik. Therefore, optimizing corporate zakat can serve as a strategic instrument to promote sustainable economic justice in Indonesia. Effective policies and outreach from the government are also needed so that companies are more encouraged to pay zakat in a timely and transparent manner.